2014
DOI: 10.1039/c4ta02303j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of triptycene-based polyimides with tunable high fractional free volume for gas separation membranes

Abstract: Triptycene-containing polyimide membranes with tunable fractional free volume promoting fast gas transport and selective separations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
152
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(163 citation statements)
references
References 47 publications
11
152
0
Order By: Relevance
“…Therefore, to overcome these drawbacks, as stated previously, the reduction of the cost of the monomer and the maintenance of excellent comprehensive properties of polymers without the sacrifice of their thermal and mechanical properties are the main design direction for chemical modifications. 29,30 Huang et al 31 reported some novel PIs; the polymers presented excellent solubility in most organic solvents and displayed good thermal stability and optical properties. Liaw et al 32 prepared several novel poly(pyridine imide)s with pendent naphthalene groups; these PIs showed excellent solubility and good thermal properties.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, to overcome these drawbacks, as stated previously, the reduction of the cost of the monomer and the maintenance of excellent comprehensive properties of polymers without the sacrifice of their thermal and mechanical properties are the main design direction for chemical modifications. 29,30 Huang et al 31 reported some novel PIs; the polymers presented excellent solubility in most organic solvents and displayed good thermal stability and optical properties. Liaw et al 32 prepared several novel poly(pyridine imide)s with pendent naphthalene groups; these PIs showed excellent solubility and good thermal properties.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, solution-processable PIMs (ladder-type and PIM-polyimides (PIM-PIs)) have been designed and predominantly evaluated for gas/gas separations (i.e. O 2 /N 2 , H 2 /N 2 , H 2 /CH 4 , CO 2 /CH 4 ) [17][18][19][20][21][22][23][24][25]. Only a few studies on PIMs, specifically the prototypical ladder-type PIM-1, have revealed outstanding vapor/gas separation properties [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the typical applications as films or varnishes for electronic/energy applications that take advantage of their thermal and mechanical stabilities, aromatic polyimides are being used in advanced technologies such as composites [7], nanomaterials [8], electrochromic [9], photomechanical [10], thermooptical [11], fuel cells [12], or gas separation membranes [13]. In addition, there is a relatively new use of certain amorphous aromatic polyimides as piezoelectric polymers [14] or magnetoelectric materials [15].…”
Section: Introductionmentioning
confidence: 99%